Analisis Pengaruh Lingkungan Kelas Terhadap Keyakinan Diri (Self-Efficacy) Murid Fase A di SDN 80/I Muara Bulian - Alifa Dwi Meiyana; Revara Gracia Venesa; Chinta Dwi Zahwa (Yayasan Al-Afif, 2026)
Classroom distractions significantly hinder early-grade literacy and numeracy development, yet their psychological impact remains understudied. This study aims to analyze the influence of classroom environment distractions on the self-efficacy of first-grade students during early calistung learning. Utilizing an empirical descriptive qualitative design, data were collected from February to March 2026 at SDN 80/I Muara Bulian through classroom observations, interviews with the homeroom teacher, and documentation involving 27 students. The results revealed that auditorial, material, and social distractions disrupted students' cognitive focus during tasks. This continuous interruption led to a sharp decline in students' psychological self-efficacy, causing profound self-doubt. Consequently, students resorted to copying peers' work as a maladaptive coping mechanism to avoid errors. In conclusion, technical calistung mastery requires adaptive classroom management that prioritizes psychological reinforcement and emotional safety over mere physical order.